تأثير الملصقات الاشهارية على مستعملي حافلات النقل العمومي -دراسة ميدانية بمدينة المسيلة. - - مراتي السعدية (جامعة محمد بوضياف بالمسيلة, 2025)
تهدف هذه الدراسة إلى التعرف على تأثير الملصقات الاشهارية على مستعملي حافلات النقل العمومي -دراسة ميدانية بمدينة المسيلة، من حيث أنواعها، مضامينها، دوافع متابعتها، ومدى تأثيرها على الجمهور المتلقي. تم استخدام المنهج الوصفي التحليلي كإطار منهجي، بالاعتماد على أداتين أساسيتين لجمع البيانات: الاستبيان الموجه إلى عينة قصدية من مستخدمي الحافلات، والملاحظة المباشرة داخل وسائل النقل العمومي. وقد تمثلت العينة في 100 مفردة، اختيروا بشكل قصدي، بما يسمح بتمثيل الفئات المستهدفة بدقة نسبية. أظهرت نتائج الدراسة ما يلي:  يعتمد عدد كبير من سكان المسيلة على الحافلات العمومية بشكل يومي.  يغلب على الإشهار داخل الحافلات الطابع التجاري، مع غياب شبه كلي للرسائل الثقافية أو التوعوية.  وصف أغلب المستجوبين درجة تركيزهم على الإشهارات بأنها متوسطة، ما يعكس محدودية التأثير البصري للمضامين الحالية.  تميل الإناث إلى تفضيل الإعلانات باللغة الإنجليزية، بينما يفضل الذكور اللغة العربية.  لا يتم استغلال الفضاء البصري داخل الحافلات بشكل احترافي، رغم إمكانية الوصول الواسع والمتكرر للجمهور.  توجد فرص واعدة لتحسين فعالية الإشهار في النقل العمومي عبر التنويع في المواضيع والتصميم واللغة. : This study aims to explore the impact of advertising posters on public bus users — a field study conducted in the city of M’sila — focusing on their types, content, motives for attention, and the extent of their influence on the target audience. The descriptive-analytical method was adopted as the methodological framework, relying on two main tools for data collection: a questionnaire directed at a purposive sample of bus users, and direct observation inside public transport vehicles. The sample consisted of 100 individuals, selected purposively, in a manner that allows for a relatively accurate representation of the targeted categories. The study yielded the following results: • A large portion of M’sila’s population relies on public buses on a daily basis. • Most of the advertisements inside buses are commercial in nature, with a near-complete absence of cultural or awareness-oriented messages. • The majority of respondents described their level of attention to bus advertisements as moderate, indicating limited visual impact. • Female respondents tended to prefer English-language ads, while male respondents favored Arabic. • Advertising spaces inside buses are not professionally utilized, despite their high visibility and constant audience exposure. • There are promising opportunities to improve advertising effectiveness through greater diversity in themes, design, and language.